2016
DOI: 10.1002/mma.3969
|View full text |Cite
|
Sign up to set email alerts
|

On the global existence of weak solution for a multiphasic incompressible fluid model with Korteweg stress

Abstract: In this paper, we study a multiphasic incompressible fluid model, called the Kazhikhov–Smagulov model, with a particular viscous stress tensor, introduced by Bresch and co‐authors, and a specific diffusive interface term introduced for the first time by Korteweg in 1901. We prove that this model is globally well posed in a 3D bounded domain. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…where ∂j denotes the generalized gradient of a prescibed locally Lipschitz function j. The boundary friction law (8) has been considered for the Navier-Stokes problems in [16,13,17,20]. Finally, the initial conditions for the velocity and concentration are prescibed…”
Section: Classical Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…where ∂j denotes the generalized gradient of a prescibed locally Lipschitz function j. The boundary friction law (8) has been considered for the Navier-Stokes problems in [16,13,17,20]. Finally, the initial conditions for the velocity and concentration are prescibed…”
Section: Classical Formulationmentioning
confidence: 99%
“…The boundary friction law (8) has been considered for the Navier-Stokes problems in [16,13,17,20]. Finally, the initial conditions for the velocity and concentration are prescibed…”
Section: Classical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…al. [6] derived versions of (1.4) without θ 2 -nonlinearity by specific choice of µ and θ. Cook-Dimotakis [7] investigated (1.2) with the constant viscosity and (1.3) to understand Rayleigh-Taylor instability between miscible fluids. Goudon-Vasseur [10] re-analyzed Kazhikhov-Smagulov type modeling of mixture flows from a more microscopic viewpoint to propose a generalized model.…”
Section: Introductionmentioning
confidence: 99%
“…This model was firstly studied in [14,1] (see also references therein). The mathematical analysis in a three-dimensional domain of KazhikhovSmagulov type models was carried out in recent works [5,8], where the authors study the Kazhikhov-Smagulov models with a specific Korteweg stress tensor. The numerical study of a Kazhikhov-Smagulov model for the two-dimensional case can be found in [4], where the authors propose an hybrid finite volume-finite element method combined with the backward Euler method in time.…”
Section: Introductionmentioning
confidence: 99%